Educational provisions of the National Training School for Girls, Marillac Hills - Galvez, Juana Respicio; Adorio, Mercedes P. (Quezon City College of Education, University of the Philippines Diliman, 1976)
The study analyzed the educational provisions at the National Training School for Girls, Marillac Hills. It provided some basic information on the education of the socially alienated youth. It gave the descriptions of socio-economic status, nature of offenses and nature of work before apprehension. Thirty school girls at the National Training School for Girls were asked to describe their educational needs and the existing educational provisions in their school by using a checklist and questionnaire. The author hopes that the study, which explored some implications of the findings in the teaching of the socially and emotionally mal-adjusted girls, will be of great help in guiding educators towards effective educational planning for this group of adolescents.
Thesis (Master of Arts in Teaching Special Education - Behavioral Problems)--University of the Philippines, Dilimanm
Keywords: Teenage girls -- Education -- Philippines -- Muntinlupa City; Poor teenagers -- Education -- Philippines -- Muntinlupa City